Case Study: A Transactional Analysis Model for a Single Mother and Her Adult Child With Bipolar Disorder. (October 2018) - Carter, David J.
This case study describes a transactional analysis model based on the strain of a single mother with an adult son suffering from bipolar I disorder. The study examines interaction patterns within the clinical setting; the therapeutic view examines contextual factors that affect this mother and her adult son through assessment and recovery with transactional analysis therapy. The 16-session therapeutic experience of a client and his mother is presented. The subjects in the case study were administered the Sixteen Personality Factor Questionnaire (16PF) assessment tool during the second and 16th sessions. There was a significant change from pretest to posttest stens scores regarding increased scores in emotional stability from 2 (extremely low) to 4 (average), rule consciousness from 1 (extremely low) to 3 (moderately low), openness to change from 6 (average) to 8 (moderately high), and self-control from 1 (extremely low) to 4 (average). Decreased scores included apprehension from 9 (extremely high) to 7 (average) and tension from 6 (average) to 3 (moderately low). Behavioral changes after a 1-month follow-up included taking the bus to sign up for a college class, taking his medication as prescribed, getting a part-time job in the kitchen at the Veteran Administration Medical Center, and developing a budget to manage his disability check.